The psychological impact of exposure to floods among adolescents - Sari, Putri Melinda; Trismiyana, Eka; Winarno, Rudi (JOURNAL OF Mental Health Concerns, 2025)
Background: Floods are the most common natural disaster in the world, dominating with 163 incidents or 50.77% in 2023. Based on the Indonesian Disaster Index (IDI) data, 8.331 flood disasters occurred in Indonesia from 2014 to 2023. Meanwhile, the National Disaster Management Agency (NDMA) recorded 16 flood incidents in the Bandar Lampung area over the past 10 years. This disaster not only causes damage to infrastructure but also instills anxiety among students, which has the potential to affect their level of preparedness. Therefore, it is very important to understand the relationship between anxiety and the preparedness of adolescents. Purpose: To determine the psychological impact of flood exposure on adolescents. Method: A Descriptive Correlational research type with a Cross Sectional approach, employing a quantitative method design with a Descriptive Correlation design. The respondents in this study are students at Junior High School 27 Bandar Lampung with a population of 469 students. The total sample obtained using Proportionate Stratified random sampling technique is 216 respondents. Results: Out of 87 students with anxiety, there were 78 (89.7%) respondents who were not prepared and 9 (10.3%) respondents who were prepared to face floods. Meanwhile, out of 129 respondents without anxiety, there were 80 (62.0%) respondents who were not prepared and 49 (38.0%) respondents who were prepared to face flood disasters. The chi-square test results showed a p-value of 0.000 < 0.05. Conclusion: Adolescence, as a dynamic transitional phase, is a crucial period for developing awareness, resilience, and preparedness in the face of disasters such as floods. Findings indicate a significant relationship between anxiety and preparedness, with adolescents experiencing anxiety being five times more likely to be unprepared than those without anxiety. Keywords: Adolescents; Anxiety; Preparedness.